2015
DOI: 10.1007/s00493-014-3081-8
|View full text |Cite
|
Sign up to set email alerts
|

Tree-width and dimension

Abstract: Abstract. Over the last 30 years, researchers have investigated connections between dimension for posets and planarity for graphs. Here we extend this line of research to the structural graph theory parameter tree-width by proving that the dimension of a finite poset is bounded in terms of its height and the tree-width of its cover graph.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…For fixed genus, this is a 2 O(h 3 ) bound on the dimension. In particular, this improves on the previous best bound for posets with planar cover graphs [9], which was doubly exponential in the height.…”
Section: Applicationssupporting
confidence: 52%
See 2 more Smart Citations
“…For fixed genus, this is a 2 O(h 3 ) bound on the dimension. In particular, this improves on the previous best bound for posets with planar cover graphs [9], which was doubly exponential in the height.…”
Section: Applicationssupporting
confidence: 52%
“…For fixed t, this is a 2 O(h t ) bound on the dimension, which improves on the doubly exponentional bound in [9]. Surprisingly, this upper bound turns out to be essentially best possible:…”
Section: Applicationsmentioning
confidence: 76%
See 1 more Smart Citation
“…We encourage readers to consult the discussion of connections between Dushnik-Miller dimension and structural graph theory as detailed in [15], [36] and [35]. Here we provide a quick summary of highlights.…”
Section: Connections With Structural Graph Theorymentioning
confidence: 99%
“…The first major result linking dimension and structural graph theory is due to Joret, Micek, Milans, Trotter, Walczak and Wang [15], who proved that the dimension of a poset is bounded as a function of its height and the tree-width of its cover graph. More formally, they showed that for each pair (t, h) of positive integers, there is a least positive integer d(t, h) so that if P is a poset of height h and the tree-width of the cover graph of P is t, then dim(P ) ≤ d(t, h).…”
Section: Connections With Structural Graph Theorymentioning
confidence: 99%